The Role of Trust in Natural Resource Management Conflicts: A Forestry Case Study from Germany. Issue 3 (28th September 2017) - Juerges, Nataly; Viedma, Alisa; Leahy, Jessica; Newig, Jens
Abstract: Managing forest use conflicts between different stakeholders is an important part of participatory forest management at the local level. Trust is thought to be an important factor in conflict management. We examined how stakeholders at a local level perceive the role of trust in the development and management of natural resource conflicts. Aggregating data from 24 qualitative semistructured interviews conducted in the German state of Lower Saxony, a conceptual model is proposed that consists of 12 factors that are perceived by the study participants to interact with the relationship between trust and conflict. On the basis of this conceptual model, we provide practical insight for forest managers about how trust can be created and maintained by those involved in participatory forest management.